EFFECT OF UNDERSTANDING OF TAXPAYERS AND SAMSAT SERVICES WITH SAMBARA APPLICATION ON COMPLIANCE WITH CIMAHI CITY MOTOR VEHICLE TAXPAYERS - Fauzian, Rusty; Betha, Maria; Ardiansyah, Ravika; Ibadurrahman, Arkan R ‘; Ramadhan, Rizqi P; Hidayat, Rachmat (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to analyze the effect of taxpayer understanding and SAMSAT services with the SAMBARA application on motor vehicle taxpayer compliance. The research was conducted in Cimahi City. The research population is all motor vehicle taxpayers. The sample was taken randomly as many as sixty motor vehicle taxpayers. The study used multiple linear regression techniques. The validity and reliability of the questionnaire are more than 0.60. The results of the study indicate that the understanding of taxpayers affects taxpayer compliance. SAMSAT service quality with the SAMBARA application affects taxpayer compliance. The understanding of taxpayers and SAMSAT services with the SAMBARA application jointly affects taxpayer compliance.